Image of Natesha in dancing posture on the Bhadra of the temple wall - Temples of India Project Team (Jio Institute, 2024)
A closer view of the east jangha (wall) of the Kumbheshwar Mahadev Temple. The wall scheme is similar to the south elevation of the temple, depicting apsaras (celestial damsels), ascetics, and dancers on the intermediate and corner projections. The bhadra (central projection) has an image of Natesha. The image of Natesha in the dancing posture shown here is six-handed, holding attributes like khatvanga (staff with a skull) and Naga. At the bottom, there are two musicians.